Uma análise sobre o papel estratégico do Exército na fronteira Brasil-Guyana na década de 1960 - Aguiar, Abílio Cunha (2016)
The international context of the Cold War influenced the events that led to the rise of the military to power in 1964. Even in the 1940s, the Brazilian military, influenced by the American school, implemented in Brazil the Higher School of War, which was the engine for organization of geopolitical and national strategic thinking. Golbery was the main designer of what later would become the National Security Doctrine, which was concerned with the sovereignty and protection of the territory. This doctrine was also against concerns about the demographic void that existed in the Amazon. Therefore, the need to "integrate to not Deliver" became the basis of the speech to the integration of the Amazon to the national context. In this set, the formation of the Federal Territories, still Getulio Vargas, was an essential part for the execution of the Amazon occupation. In this sense the Brazilian Army played an extremely important role in the entire Amazon region, and here we stress the Roraima’s case, especially in the late 1960. In this period occurred in the Guyana's Rupununi uprising, which was of great influence on the structure of the army in Roraima. This research aims to examine the role of the army in this border during the 1960s, based on the international context, national and local. For this use we will primary sources of consulting books, theses, articles and dissertations on the subject